A COMPARATIVE ANALYSIS OF STUDENTS' READING ACHIEVEMENT USING MULTIPLE-CHOICE AND ESSAY TESTS - Fathur Rahman Saut Matua Situmorang; Baso Jabu; Geminastiti Sakkir (Universitas Negeri Makassar, 2026)
This study aimed to compare students’ reading achievement as measured by multiple-choice and essay tests and to determine whether a significant difference existed between the two assessment formats in measuring reading ability. The study employed a quantitative comparative design and was conducted at SMPN 40 Makassar during the 2025/2026 academic year. The participants consisted of 32 eighth-grade students selected through cluster random sampling. Two reading comprehension tests, namely a multiple-choice test and an essay test, were developed based on identical reading indicators, including identifying main ideas, locating detailed information, interpreting vocabulary in context, making inferences, and identifying the author’s purpose. The collected data were analyzed using descriptive statistics, validity and reliability testing, the Shapiro–Wilk normality test, and the Wilcoxon Signed-Rank Test. The results revealed that the mean score obtained from the multiple-choice test was 78.75, while the mean score from the essay test was 77.81, resulting in a mean difference of 0.94. The Wilcoxon Signed-Rank Test showed no statistically significant difference between the two test formats (Asymp. Sig. = 0.583, p > 0.05). These results indicate that both multiple-choice and essay tests provide comparable measurements of students’ reading achievement when constructed based on the same reading objectives and assessment indicators. Therefore, both assessment formats can be effectively used to evaluate students’ reading ability, and their combined use may provide a more comprehensive assessment of students’ reading performance.